Seroprevalence and associated risk factors of caprine arthritis encephalitis (CAE) and peste des petits ruminants (PPR) among deer in an institutional farm in Malaysia - Balakrishnan, Krishnan Nair; Jesse, Faez Firdaus Abdullah; Paul, Bura Thlama; Charles, Shalonagiftsal Stephen C; Noor Zaman, Ummul Rifhan Najiha; Teik Chung, Eric Lim; Azhar, Nur Amira; Barre, Abdirahman; Mikail, Muhammed; Mohd Lila, Mohd Azmi (Chulalongkorn University Printing House, 2025)
Caprine arthritis encephalitis (CAE) and peste des petits ruminants (PPR) are significant viral diseases impacting small ruminants, leading to substantial economic losses and posing a potential threat to livestock health. Although seroprevalence evidence of these viruses has been documented in ruminants, there is a lack of data regarding their presence among farmed deer in Malaysia. This preliminary study aimed to determine the seroprevalence and associated risk factors for CAEV and PPRV infections among deer in Malaysia. A total of ninety-two blood sera from an institutional deer farm were screened for CAEV and PPRV antibodies using commercially available indirect ELISA test kits. The results revealed 8.7% (95% CI = 4.47-16.23) apparent and 8.38% (95% CI = 3.72-16.7) true prevalence for CAEV and 4.35% (95% CI = 1.70-10.65) apparent and 3.99% (95% CI = 1.18-10.70) true seroprevalence for PPRV among deer. Univariable analysis indicated that age (χ2 = 4.434, p = 0.707) and sex (χ2 = 1.071, p = 0.377) were not significantly associated with CAEV seropositivity, while the herd group (χ2 = 4.733, p = 0.053) showed a significant association. Conversely, PPR seroprevalence was higher in young deer (8.0%) compared to adults (2.69%), with female deer demonstrating a higher prevalence (5.36%) than males. Additionally, the older herd exhibited a higher true prevalence of PPR (5.07%) compared to the newer herd (2.32%). This study provides the first serological evidence of CAEV and PPRV among deer in Malaysia and justifies further epidemiological investigations in order to reduce the potential threat to animals.